Plant‐supported silver nanoparticles: Efficient, economically viable and easily recoverable catalyst for the reduction of organic pollutants. (28th May 2019) - Ismail, Muhammad; Khan, M.I.; Khan, Murad Ali; Akhtar, Kalsoom; Asiri, Abdullah M.; Khan, Sher Bahadar
Abstract : Ginger rhizome powder was used for the synthesis of supported metallic nanoparticle catalysts. A simple and novel adsorption method was used for the synthesis of silver nanoparticles loaded on ginger powder (Ag/GP), copper on ginger powder (Cu/GP) and nickel on ginger powder (Ni/GP). Among these, Ag/GP showed selective reduction of methyl orange and was used for further reactions. The prepared nanomaterials were characterized through X‐ray diffraction, transmission electron microscopy, field emission scanning electron microscopy, fourier transform infrared spectroscopy and energy‐dispersive X‐ray spectroscopy. The prepared Ag/GP catalyst was employed in the catalytic reduction of 4‐nitrophenol (4‐NP), 2‐nitrophenol (2‐NP), rhodamine B, methyl red and congo red. Ag/GP showed excellent catalytic reduction activity, the rate constants being 1.26 × 10 −3 and 2.38 × 10 −3  s −1 for 2‐NP and 4‐NP, respectively. The turnover frequency reached 1.06 min −1 for 2‐NP and 1.16 min −1 for 4‐NP when using the Ag/GP catalyst. The prepared Ag/GP catalyst demonstrated outstanding activity for the degradation of a mixed solution of dyes. Also, stability and reusability of the prepared catalyst were investigated, which showed outstanding reusability up to five times and was stable up to five days. Abstract : Here in this study, simple, cost‐effective and novel adsorption method was used for in situ synthesis of ginger powder supported silver nanoparticles (Ag/GP). The prepared Ag/GP catalyst was employed in the remediation of toxic nitrophenols and carcinogenic dyes separately as well as collectively. Considering the novel preparationmethod, the sustainable plant materials that could be derived on huge quantities, stability and reusability; the process can be developed for the synthesis of stable and reusable inorganic catalytic materials for water purification.